Monitoring Drug Safety Information - Recommendations of Foreign Regulatory Authorities - Elena V. Shubnikova; Marya A. Darmostukova; Irina I. Snegireva; Evgeniya O. Zhuravleva (Безопасность и риск фармакотерапии, 2020)
Analysis of administrative decisions of foreign regulatory authorities on the recoil of medicines and/or the need for changes in the instructions for their medical use due to changes in the safety proﬁ le, conducted by experts of the Scientiﬁ c Centre for Expert Evaluation of Medicinal Products revealed 16 administrative decisions. These decisions contained information on the following medicines registered in Russia: norepinephrine, xylometazoline, mometason, liraglutide recombinant, exenatide, insulin recombinant human, insulin degludec, teriparatide, progesterone, gestodene, desogestrel, dienogest, drospirenone, norgestrel, lynestrenol, levonorgestrel, medroxyprogesterone, mestranol, nomegestrol, norethisterone, norgestimate, chlormadinone, cyproterone, estradiol, ethinylestradiol, etonogestrel, ethinylestradiol, ﬁ nasteride, abiraterone, thiamazole, omega-3-acid ethyl esters, pitavastatin.